'An Incomplete Contract Approach to Eurozone Fiscal Governance' – Commitment vs. Flexibility. Issue 2 (3rd April 2017) - Suzuki, Yutaka; Tsuranuki, Yoshihiro
ABSTRACT: In this paper, we take an incomplete contract approach to Eurozone Fiscal Governance between the European Commission (EC) and any heavily debt member state, Greece in particular. Incomplete contract approach makes possible to put a long process of Eurozone Fiscal Governance into an extensive form game in which a renegotiation procedure is incorporated. We theoretically reveal the conflict of interests between the EC (Germany) and Greece over the Greek debt repayment plan proposed in 2015. We show that the Greek's position is consistent with incomplete contract theory, but that the EC (Germany) does not allow the renegotiation for restructuring for growth-oriented debt repayment program proposed by the Greek government because the EC (Germany) judges that the commitment effect (on fiscal austerity) is greater than the flexibility one (pro-growth effect). This will undoubtedly provide a novel and interesting approach to Eurozone Fiscal Governance.